Healing the Healers: Support for Psychiatrists After Patient Suicide - NUR IWANA, ABDUL TAIB; MUHAMMAD HANIF, ABD LATIF; NURAZAH, ISMAIL; ABDUL HAKEM, ZAHARI; TUTI IRYANI, MOHD DAUD; RAVIVARMA RAO, PANIRSELVAM; JOHARI, KHAMIS; AHMAD ROSTAM, MD ZIN; HAZLI, ZAKARIA (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2024)
The aftermath of a patient’s suicide can significantly impact psychiatrists, often leading to intense feelings of grief, guilt, and professional doubt. This symposium explores effective support mechanisms tailored to the needs of Malaysian psychiatrists facing such challenging circumstances. A recent study identified several support mechanisms that respondents found beneficial and necessary. Key recommendations for supporting psychiatrists include: (i) Personal Debriefing: Providing opportunities for psychiatrists to debrief personally can help them process their emotions and experiences in a safe, confidential environment. This practice enables them to articulate their feelings and receive immediate psychological support. (ii) Assistance with Communication: It is crucial to help psychiatrists communicate or meet with the patient’s family and friends. Such interactions can be emotionally charged and complex; thus, guidance and support in these situations can alleviate some of the associated stress and uncertainty. (iii) Senior Clinician Involvement: Senior clinicians’ involvement in the support process is vital. Their experience and authority can provide reassurance and mentorship, helping junior psychiatrists navigate the professional and emotional challenges following a patient’s suicide. (iv) Peer Support: Establishing peer support networks allows psychiatrists to share their experiences and coping strategies with colleagues who understand their unique challenges. This collegial support fosters a sense of community and mutual understanding. (v) Informational Resources: Providing comprehensive information about the processes following a patient’s death by suicide, including procedural steps and available resources for affected families, ensures psychiatrists are well-informed and better prepared to handle the aftermath. This symposium will explore these recommendations, discussing practical guidance and strategies to implement these support mechanisms effectively. By fostering a supportive environment and addressing the specific needs of psychiatrists, we aim to mitigate the emotional toll of patient suicide and promote resilience and well-being within the psychiatric community.